Coating (Coating to Optimize Aneurysm Treatment in the New Flow Diverter Generation) study. The first randomized controlled trial evaluating a coated flow diverter (p64 MW HPC): study design - Pierot, Laurent; Lamin, Saleh; Barreau, Xavier; Berlis, Ansgar; Ciceri, Elisa; Cohen, José E; Costalat, Vincent; Eker, Omer F; Henkes, Hans; Holtmannspötter, Markus; Januel, Anne-Christine; Keston, Peter; et al. (Journal of neurointerventional surgery, 2023)
BackgroundDue to its high efficacy, flow diversion is increasingly used in the management of unruptured and recanalized aneurysms. Because of the need for perioperative dual antiplatelet treatment (DAPT), flow diversion is not indicated for the treatment of ruptured aneurysms. To overcome this major limitation, surface modification—‘coating’—of flow diverters has been developed to reduce platelet aggregation on the implanted device, reduce thromboembolic complications, and facilitate the use of coated flow diverter treatment in patients with single antiplatelet treatment (SAPT). COATING (Coating to Optimize Aneurysm Treatment in the New Flow Diverter Generation) is a prospective, randomized, multicenter trial that aims to determine whether the use of the coated flow diverter p64 MW HPC under SAPT is non-inferior (or even superior) to the use of the bare flow diverter p64 MW under DAPT in relation to thromboembolic and hemorrhagic complications.MethodsPatients with unruptured or recanalized aneurysms for which endovascular treatment with a flow diverter is indicated will be enrolled and randomly assigned on a 1:1 ratio to one of two treatment groups: p64 MW HPC with SAPT or p64 MW with DAPT.ResultsThe primary endpoint is the number of diffusion-weighted imaging lesions visualized via MRI assessed within 48 hours (±24 hours) of the index procedure. Secondary primary endpoints are comparing safety and efficacy in both arms.ConclusionsThis randomized controlled trial is the first to directly compare safety and efficacy of coated flow diverters under SAPT with bare flow diverters under DAPT.Trial registration number http://clinicaltrials.gov/ - NCT04870047.